BIMBINGAN PRIBADI-SOSIAL BERBASI ZOOM MEETING UNTUK KONSEP DIRI POSITIF PESERTA DIDIK SMP KELAS IX - Selly Rizky Yuliana; Wahyu Hidayat; Siti Fatimah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
This research  is  motivated by  the  existence of  a  negative self-concept  in  class IX  students.  This is  indicated  by the  behavior  that is  not  in accordance  with  the behavior  of  students at  school.  This study  uses  a qualitative  descriptive  method with  the  aim of  describing  the implementation  of  pribadi-social  guidance. The  results  of the  research  obtained in  the  implementation  of pribadi-social  guidance  using a  zoom  meeting, namely  planning  first then  carrying  out services  through  several stages  such  as problems,  diagnosis,  prognosis, therapy  and  evaluation and  follow-up.  This can  be  seen from  inappropriate  behaviors such  as  not liking  criticism,  withdrawing from  friends  and not  understanding  himself, his  family,  and the  people  around him.  Social  interaction is  also  hampered and  makes  it difficult  for  these students  to  develop their  potentialKeywords: Pribadi-Social  Guidance,  Self-Concept, Zoom  Meeting,  Learners